OPTIMASI PENENTUAN LOKASI INDUSTRI DENGAN GIS-MCA: INTEGRASI TEKNOLOGI UNTUK ANALISIS SPASIAL MENDALAM - Nur, Ahmad Amri; Sandri, Dian; Haidar Ahmada, Naufal; Aulia Purbandini, Revi (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2024)
and extinction if its location does not match its purpose. Each region requires an Industrial Designation Area for economic development, activity separation, environmental management and infrastructure development. The purpose of this study is to identify and find the location of the Industrial Designation Area in Purbalingga Regency that meets the technical criteria totaling seventeen criteria. These criteria are weighted through the Analysis Hierarchy Process technique to obtain the level of importance of all criteria by expert opinion. The method used is Spatial Multicriteria Analysis using the ArcGIS map processor. The results of the study show that the location of the Industrial Designation Area that is very suitable in Purbalingga Regency is 2,165 Ha spread across Bukateja, Kemangkon, Purbalingga and Kalimanah Districts. In-depth spatial analysis shows that the Very Suitable location is supported by the existence of a planned toll road, station, airport and is still close to the city center. The seventeen criteria used produce three categories of industrial area suitability levels, namely Very Suitable covering an area of ​​2,165 Ha, Suitable covering an area of ​​2,123 Ha and Quite Suitable covering 8,071 Ha.